Sex Differences in the Association between Heavy Drinking and Behavioral Distress Tolerance and Emotional Reactivity Among Non-Depressed College Students. (27th June 2018) - Pedrelli, Paola; MacPherson, Laura; Khan, Amanda J; Shapero, Benjamin G; Fisher, Lauren B; Nyer, Maren; Cassano, Paolo; Parnarouskis, Lindsey; Farabaugh, Amy; Fava, Maurizio; Silveri, Marisa M
Abstract : The study examined two constructs consistent with negative reinforcement processes, behavioral distress tolerance (DT) and emotional reactivity (frustration reactivity and irritability reactivity), to explain heavy episodic drinking (HED) among non-depressed college students. Behavioral DT and frustration reactivity independently predicted HED. Higher HED was associated with higher frustration reactivity and lower behavioral DT in women, but nor in men. Abstract: Background: Heavy episodic drinking (HED) is a common behavior among college students that is associated with severe negative consequences. Negative reinforcement processes have been applied to elucidate mechanisms underlying relationships between consumption of alcohol and the desire to alleviate negative feelings. Distress tolerance (DT) and emotional reactivity are two mechanisms that are consistent with the self-medication model that may contribute to HED. The current study investigated relationships between DT, emotional reactivity, defined as frustration reactivity and irritability reactivity, and HED in a non-depressed college population. Given differential patterns of consumption and motivation for drinking between males and females, sex differences were also examined. Short Summary: The study examined two constructs consistent with negative reinforcement processes, behavioral distress tolerance (DT) and emotional reactivity (frustration reactivity and irritability reactivity), to explain heavy episodic drinking (HED) among non-depressed college students. Behavioral DT and frustration reactivity independently predicted HED. Higher HED was associated with higher frustration reactivity and lower behavioral DT in women, but nor in men. Methods: One-hundred-ten college students without depressive symptoms completed alcohol use measures and the Paced Auditory Serial Attention Task (PASAT-C) to assess behavioral DT and emotional reactivity. Results: DT and frustration reactivity independently predicted HED. The association between DT and HED was moderated by sex such that higher levels of DT predicted higher HED among females, but not among males. Higher frustration reactivity scores were associated with a greater number of HED. Conclusions: Results provide supporting evidence that DT and emotional reactivity are distinct factors, and that they predict HED independently. Results underscore the importance of examining sex differences when evaluating the association between HED and negative reinforcement processes in this population.